INQUIRY-BASED EDUCATION IN TECHNICAL EDUCATION - STEBILA, Jan; KOZUCHOVA, Maria; BARNOVA, Silvia (Journal of Technology and Information Education, 2024)
In the article, we summarize some of the results obtained by researching the gradual implementation of innovative educational strategies (in the most recent case Inquiry-Based Education - further IBSE) to technical education at Slovak primary schools. The article shows the justification for the use of IBSE in teaching the subject Technology in lower secondary education. Thus, we focus in detail on the gradual implementation of innovative educational strategies into technical education at Slovak primary schools. The results point to the justification for the use of IBSE in teaching the subject Technology in lower secondary education.
Keywords: Inquiry-Based Education; Technical Education; Research; Teacher